IMPLEMENTASI GOOD CORPORATE GOVERNANCE DI PT. MEDAN RAYA PERKASA - Gulo, Nifarius; Rajaguguk, Particia Herpayanti; Siagian, Nalom (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
During the internship at PT. Medan Raya Perkasa, the author gained experience in understanding something in the world of work, especially in the business administration department and legal division. During the internship, the author carried out various activities during the internship such as preparing documents, filing letters, calculating taxes, preparing minutes of handover of houses/properties until the author was involved in the process of handover of houses/properties, the author learned the procedures in the house agreement process, the process of purchasing a house through a mortgage, the process for binding a sales and purchase agreement (PPJB). This experience helped improve the author's skills, especially in the business administration department, responsibility, and adaptability in a professional environment. From the author's observations of the implementation of Good Corporate Governance (GCG) at PT. Medan Raya Perkasa, it has been running well through the five (5) main principles of GCG, namely transparency, accountability, responsibility, independence, and fairness.